Engineering Hall, University of Washington, Seattle, approximately 1918 - Linkletter, L.G.
Built in 1908 this was the Machinery Hall during the Alaska Yukon Pacific Exposition. Caption on image: Machinery Hall. U. of W. L.G. Linkletter. PH Coll 95.6 L.G. Linkletter worked as a photographer in the University District from 1906 till his death in 1937. He photographed many University events, buildings and students and was also known for his images of Mount Rainier National Park.